Analysis of Employee Well-being among Part-Time Student Workers in Micro, Small, and Medium Enterprises (MSMEs) based on Demographic Characteristics - Ulya, Laila Listiana; Dian Nugrahani Ayuningtyas; Nur Rohman (Universitas Medan Area, 2025)
This study aims to describe the demographic characteristics and the level of employee well-being (EWB) among university students working part-time in Micro, Small, and Medium Enterprises (MSMEs), as well as to analyze the relationship and influence of demographic variables on the three core dimensions of EWB: Life Well-being (LWB), Workplace Well-being (WWB), and Psychological Well-being (PWB). Using a quantitative approach, data were collected from 496 respondents selected through purposive sampling. The data were gathered via an online questionnaire and analyzed using descriptive statistics, Pearson correlation, and multiple linear regression. The results show that many respondents were female, 21 years old, enrolled in public universities, in their final semester, and working in the small-scale food and beverage sector. Overall, EWB levels were relatively high, particularly in the WWB and PWB dimensions, while LWB was at a moderate level. Age, type of university, and semester showed significant but weak relationships and influences on certain dimensions of well-being. These findings highlight the need for greater support to enhance the well-being of student workers in informal employment settings.